Mental health care in Anglophone West Africa (2014)
This column describes the current state of resources and practice in mental health care in the Anglophone countries of West Africa: the Gambia, Sierra Leone, Ghana, Nigeria, and Liberia. Information was systematically gathered from the five countries by using a standard framework for country situation analysis. Mental health services, which are in various stages of development, are characterized by inadequate human resources and long policy neglect. Despite the low numbers of specialists, the region has made important contributions to community service development and global mental health research. Challenges include man power development, policy and legislation updates, and increased attention to policy and budget. Although mental health service is still grossly inadequate in the con text of human and material constraints, there are slowly evolving signs of positive modernization and service development.